Up-Regulation of Myocardial L-Type Ca2+ Channel in Chronic Alcoholic Subjects Without Cardiomyopathy - Fatjó, Francesc; Sancho-Bru, Pau; Fernández-Solà, Joaquim; Sacanella, Emilio; Estruch, Ramón; Bataller, Ramón; Nicolás, Josep-María (Alcoholism, clinical and experimental research, 2007)
Background: Excessive ethanol intake is one of the most frequent causes of acquired dilated cardiomyopathy in developed countries. L‐type Ca2+ channels, involved in excitation–contraction coupling, are disturbed in animal models of persistent ethanol consumption. This study was designed to evaluate the density and function of myocardial L‐type Ca2+ channel receptors in organ donors with chronic alcoholism and controls. Methods: The protein expression of L‐type Ca2+ channels was determined with 3H‐(+)‐PN 200‐110‐binding experiments using a specific antibody against the α1‐subunit in homogenate samples of left‐ventricle apex from organ donors: healthy controls (n=11), chronic alcoholic without cardiomyopathy (n=12), and alcoholics with cardiomyopathy (n=11). Morphometric measurements of cardiomyocytes were performed. Results: Binding experiments proved an up‐regulation of L‐type Ca2+ channels expression in alcoholic patients compared with controls (Bmax 2.61 ± 1.10 vs 1.33 ± 0.49 fmol/mg, respectively; p<0.001). This up‐regulation was present in the group of alcoholic subjects without cardiomyopathy, and was not seen in those with cardiomyopathy (3.39 ± 2.20 vs 1.77 ± 0.53 fmol/mg, respectively; p=0.02). The cross‐sectional area and perimeter of the cells were greater in alcoholic patients with cardiomyopathy compared with controls and alcoholic patients without cardiomyopathy (500 ± 87 vs 307 ± 74 and 255 ± 25 μm2, respectively; p<0.001 both) as was the perimeter (78.7 ± 7.7 vs 61.5 ± 7.2 and 56.5 ± 2.8 μm, respectively; p<0.001 both). Binding results did not change after adjusting receptor measurements for cross‐sectional area and cell perimeter. Conclusions: Chronic alcoholism causes an up‐regulation of myocardial L‐type Ca2+ channel receptors, which decreases when cardiomyopathy is present.